"How long does crizotinib work? a rare case of recurrent inflammatory myofibroblastic tumor". Issue 1 (January 2022) - Albayrak, Haluk Cihad; Gürler, Fatih; Sütçüoğlu, Osman; Akyürek, Nalan; Özet, Ahmet
Abstract : Inflammatory myofibroblastic tumors (IMTs) are mesenchymal solid tumors, in which anaplastic lymphoma kinase (ALK) gene rearrangement might be detected. A 48-year-old female presented with IMT of lung, treated with surgery. After a 39-month disease-free survival metastatic recurrence was occurred involving soft tissues both infra- and supradiaphragmatic regions. The biopsies obtained from metastatic regions confirmed the recurrence with ALK rearrangement in immunohistochemistry. Initial partial response observed early in treatment course remained as a stable disease with crizotinib treatment. Although an excellent outcome with overall survival of 57 months was observed in our case, there is not enough information about survivals with crizotinib and the treatment options beyond progression. Therefore, every individual case has a unique value paving the way for more effective treatment.